Сутність витрат птахівництва та чинники їх формування в системі управлінського обліку підприємства - Саванчук, Тетяна Миколаївна; Savanchuk, Tetіana; Френкель, Ольга; Frenkel, Olga (My University, 2023)
У статті визначено сутність категорії «витрати» та виділено основні чинники, що на них впливають на підприємствах галузі птахівництва, що дозволило виокремити перспективні напрямки організації управлінського обліку таких витрат. Визначено, що в галузі птахівництва в Україні в останні роки спостерігається зниження обсягів виробництва продукції, що вимагає підвищення уваги до інформаційного забезпечення прийняття управлінських рішень з метою оптимізації витрат виробництва. Особлива увага в статті приділяється виділенню специфічних чинників, що впливають на витрати галузі птахівництва та заходів, які здатні підтримувати рентабельність даної галузі. Встановлено, що система управлінського обліку має бути максимально налаштована на інформаційне забезпечення ефективного управління всіма виробничими процесами і вмонтована в систему фінансового обліку підприємства. The purpose of the article is to define the essence of the "expenses" category, to highlight the main factors that affect them at enterprises in the poultry industry and promising directions for the organization of management accounting of such costs. A high-quality organization of management accounting of production costs in the poultry industry will provide management with the necessary information for making management decisions. This determines the relevance of the research. The research was conducted using the monographic method. The article determines that in the poultry industry in Ukraine, in recent years, there has been a decrease in the volume of production, which requires increased attention to the information support of management decision-making. The authors established the essence of the "expenses" category based on the study of literary sources. Particular attention is paid in the article to the selection of the main factors affecting the costs of enterprises in the poultry industry. It has been proven that the management accounting system should be maximally configured for information support of effective management of all production processes and incorporated into the company's financial accounting system. It should ensure the possibility of controlling the costs of feeding, maintenance, treatment and other aspects of poultry farming, tracking the volume and state of resource stocks necessary for the production of poultry products, the quantity and quality of poultry products, assessing the financial efficiency of the enterprise, generating reports and analyzing financial indicators . The management accounting system should provide information on the required amount of investments. It is advisable to check and improve accounting processes on the basis of building an internal audit system. The accounting system should form information on compliance with the standards and rules of production of poultry products to ensure control of product safety and quality. The article contains practical advice on the areas of organization of management accounting that can be used by poultry enterprises.
The essence of poultry costs and factors of their formation in the enterprise management accounting system
Keywords: витрати; Costs; виробництво; production; управлінський облік; management accounting; птахівництво; poultry farming; управління; management